MODEL PERTUMBUHAN LOGISTIK PREDATOR DAN PREY PADA POPULASI PREY DAN SOLUSI KESETIMBANGAN - Sunarsih, Sunarsih; Hidayati, Firsty Nur (JURNAL SAINS DAN MATEMATIKA, 2010)
ABTRACT– A predator-prey model with logistic growth in the prey population is an iknteraction between a predator and a prey population with logistic growth in the prey population. The equations in this model are non linear dffirentiat equation with two dependent variables. In this system, H(t) X size of prey population at time t and P(t) is size of predator population at time t . This model have three equilibria.Key words : logistic, predator and prey, equilibrium pointPermalink : http://ejournal.undip.ac.id/index.php/sm/article/view/3118